Back Cover: Hierarchical Ternary MoO2/MoS2/Heteroatom‐Doped Carbon Hybrid Materials for High‐Performance Lithium‐Ion Storage (ChemElectroChem 6/2016). Issue 6 (13th May 2016) - Liu, Haidong; Hu, Huating; Wang, Jun; Niehoff, Philip; He, Xin; Paillard, Elie; Eder, Dominik; Winter, Martin; Li, Jie
Abstract : The Back Cover picture illustrates how three components (MoO2 /MoS2 /heteroatom‐doped carbon) can be hybridized as a novel hierarchical architecture through a one‐pot solvothermal process with the assistance of an ionic liquid and a polymer, which reveals an attractive electrochemical performance for lithium‐ion storage. More information can be found in the Full Paper by J. Li and co‐workers onpage 922 in Issue 6, 2016 (DOI:10.1002/celc.201600062 ).